KEBIJAKAN SINGAPURA MEMPERTAHANKAN KERJASAMA DENGAN ISRAEL DALAM BIDANG PERTAHANAN KEAMANAN - Harun Umar; Melati Nasional Rambu Bangi (Universitas Nasional, 2010)
In military cooperation with Israel, Singapore takes two interests sharply; economy and security defense. For that reason, it is important to describe the aim of Singapore in keeping its military cooperation with Israel. The security of Malacca Strait herein is very crucial for Singapore’s economy.